The Effect of Motivation, Leadership Style, and Work Discipline on Employee Performance - Sugesti Nadya; Armalia Reny WA; Yudhinanto CN; M. Renandi Ekatama Surya; Susi Indriyani; Hasbullah Hasbullah; Desmon Desmon; Maria Septijantini Alie (Journal of Multidisciplinary Academic and Practice Studies, 2026)
Purpose: This study aimed to investigate the influence of motivation, leadership style, and work discipline on employee performance at the Administrative Bureau of the Regional Secretariat of Lampung Province, Indonesia. Research Methodology: This study used a quantitative descriptive approach. Data were collected from 96 civil servants using structured questionnaires measured on a five-point Likert scale. Instrument validity was assessed using Pearson product-moment correlation, and reliability was confirmed using Cronbach's alpha. Results: The coefficient of determination (R²) was 0.981, indicating that motivation, leadership style, and work discipline together explained 98.1% of the variance in employee performance. The F-test showed a statistically significant simultaneous effect (F = 1,596.868; p < 0.05). Partial t-tests revealed that leadership style (β = 1.060; t = 17.439; p < 0.05) and work discipline (β = 0.736; t = 9.320; p < 0.05) positively and significantly affected performance, whereas motivation had a significant negative partial effect (β = −0.517; t = −6.174; p < 0.05). Conclusions: Leadership and discipline strongly drive performance in this bureaucratic setting, whereas intrinsic motivation may be less effective due to formal control mechanisms. Limitations: The study was limited to one bureau and cross-sectional data; thus, the results may not be generalized broadly. Other contextual factors may influence the negative effects of motivation. Contributions: Highlights the need for HR policies that balance motivation with leadership and discipline to optimize civil servant performance.